ENTREPRENEURSHIP ORIENTATION AND MARKET PERFORMANCE: MEDIATING ROLE OF LEARNINGCAPABILITY - Zehir, Cemal; Klrali, Aysegul Eryilmaz; Ozgul, Burcu; Akdag, Hakan (FUTURE ACAD, 2019)
Aim of the research is to exhibit the mediating role of the learning capability in relation between the entrepreneurship orientation and market performance of firms, to expand the literature in this area and to make a contribution. Intended for this aim, a theoretical framework and hypothesis that investigate the mediating effect have been developed. A quantitative analysis on this theoretical framework has been carried out, sets of results have been attained through the scale used making use of the data provided from 215 intermediate and senior managers who are working in firms active in manufacturing industry. In first part of the survey, demographic information's were questioned to define characteristics of firms and people filling the form. In second part, there is learning capability, market leading strategies and finally firm performance scale which is the dependent variable. The results show that there is a strong relation between the entrepreneurship orientation and market performance and the learning capability of an organization partly effects the relationship between these two concepts. At the turn of this analysis, some suggestions for researchers based on the findings obtained have been submitted. (C) 2019 Published by Future Academy www.FutureAcademy.org.UK
Keywords: Entrepreneurship orientation; organizational learning capability; market performance; BUSINESS PERFORMANCE; CORPORATE ENTREPRENEURSHIP; FIRM PERFORMANCE; INNOVATION; CONSTRUCT; STRATEGY; LINKING; IMPACT; Business & Economics